#TITLE_ALTERNATIVE# - Hasjim (NIM 250 96 062), Iswan
Abstract : The non linear hydrodynamic force analysis show that it is possible that resonansi will happen in Tension Leg Platform. The non linear force is obtained by using Bernoullis equation in term of non linear. The method of Freude Krylov indicate possible resonance phenomenon which occur at lower frequency (sub harmonic) and higher frequency (super harmonic). Actually, non linear force is fairly small but resonance case still possible occur and magnify the Tension Leg Platform response.